OPTIMASI JALUR DISTRIBUSI PADA UMKM MITRA TELUR DENGAN MENGGUNAKAN METODE SAVING MATRIX DAN NEAREST NEIGHBOR - Muhammad Aqil Siraj (JURNAL ILMIAH SAINS TEKNOLOGI DAN INFORMASI, 2024)
Mitra Telur is an egg producer located in Pirakbulus, Sidumulyo, Godean District, Sleman Regency, Special Region of Yogyakarta. So far, Mitra Telur UMKM has not determined a travel route to distribute the eggs. The distribution carried out does not take into account the distance traveled to reach the shop points. This research uses two methods at once, namely saving matrix and nearest neighbor. Based on the calculation results, the initial route has a total distance of 114.9km with 4 delivery routes, while the final route has a total distance of 95.5km with 3 delivery routes. The initial route has a fixed cost of IDR 1,550,000 and a variable cost of IDR 402,150 with a total delivery cost of IDR 1,952,150, while the final route has a fixed cost of IDR 1,550,000 and a variable cost of IDR 334,250 with a total delivery cost of IDR 1,884,250. there was a reduction in distribution routes by 16.9% and a reduction in production costs by 3.5%.